MANAJEMEN PEMBIAYAAN SEKOLAH - Sita Pancarini; Diah Soepini; Rizki Yanto (UNISAN JURNAL, 2022)
The purpose of this research is to find out how school financing is managed. The research method used in this study is a qualitative method. The results of the study show that education is the sector that incurs the most significant tax costs from the government. The field of economics can be understood as a study of how people or society choose to use money and other limited or scarce resources to produce or achieve unlimited wants. One thing that is important to the new thinking that education is considered as a form of investment (Human Investment). Where this concept states that people who have certain skills, habits and knowledge they can sell in the form of work to earn wages or salaries, so that they can be played as a resource throughout their lives. Furthermore, this "human capital" can be analogous to physical capital because both are used to generate steady income for many years. School as one of the institutions that carry out educational activities is a production process that produces quality graduates so that it is necessary to manage financing so that the quality of graduates can compete for a decent life in the midst of society.